1985
DOI: 10.1099/00221287-131-4-737
|View full text |Cite
|
Sign up to set email alerts
|

Selection for Nonadherent or Nonhydrophobic Mutants Co-selects for Nonspreading Mutants of Cytophaga johnsonae and Other Gliding Bacteria

Abstract: Predictions based on a general model of surface components involved in gliding motility of Cytophaga johnsonae along with characteristics of previously isolated nonspreading mutants of C. johnsonae led us to suspect that isolation of such mutants could be accomplished by selecting for nonadherent or nonhydrophobic mutants. Accordingly, conditions were devised to select for mutants that failed to attach to cheesecloth suspended in growth media and for mutants that failed to adhere to n-hexadecane droplets. Popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
66
0

Year Published

1986
1986
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 33 publications
(67 citation statements)
references
References 9 publications
1
66
0
Order By: Relevance
“…Earlier results (Pate at al., 1979;Chang at al.. 1984;Wolkin & Pate, 1985) suggested that the TNM pleiotropy is produced by any condition that stops motility. Three approaches to test this idea are: (i) to isolate and test many TNM mutants; (ii) to attempt to isolate phages that will infect TNM mutants; and (iii) to determine whether inhibiting motility of wild-type cells induces the TNM pleiotropy.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Earlier results (Pate at al., 1979;Chang at al.. 1984;Wolkin & Pate, 1985) suggested that the TNM pleiotropy is produced by any condition that stops motility. Three approaches to test this idea are: (i) to isolate and test many TNM mutants; (ii) to attempt to isolate phages that will infect TNM mutants; and (iii) to determine whether inhibiting motility of wild-type cells induces the TNM pleiotropy.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of over 250 independently isolated TNM mutants suggested that anything that stops motility invariably results in the TNM pleiotropy, not because of alteration or !oss of a specific cell component or inability to supply an intermediate required for expression of all affected characteristics, but because motility itself is required for their expression (Pate et Chang et Wolkin & Pate, 1985). In the present work, we tested this idea by determining whether chemicals that stop motility of wild-type cells confer the TNM pleiotropy on wild-type cells.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations